Studies of electric discharges and their interactions with gases - Qiulin Yuan (1997)
Measurements of the effect of increasing the discharge column voltage gradient were investigated using argon based mixtures with nitrogen, oxygen and sulphur hexafluoride in a plasma torch. The theoretical calculation of the voltage gradient and the electron number density was based on the Saha equation which was modified for application to the gas mixtures. The investigations showed that a mixture of Ar and SF6 was most effective and increased the voltage gradient to 0.5 V/mm from 0.3 V/mm. The best mixture was 89% Ar, 10% N2 , 1% SF6 based on the highest increase of the voltage gradient and the least added gas. A model has been developed to illustrate the effects of dissociation, excitation, ionisation of gases and their effects on the discharge column voltage gradient: The mode of an electric discharge in Ar was investigated using spectroscopy. The study showed that for a glow discharge the 520.0 nm line and for an arc discharge the 427.1 nm line were unique. These lines were used to investigate a Glydarc electric discharge which was shown to be a mixture of the glow and the arc discharges. Measurements of the transition of the glow to arc in Ar with discharge current ranging from 0.1 A to 1.0 A at atmospheric pressure showed that at the lower value of discharge current (O. 25 A) the spectral lines were dominated by the near infra-red lines whereas at the higher value of discharge current (1.0 A) the spectral lines were included from the near infra-red to the near UV. The Glydarc electric discharge has been studied in still and fast air flows at atmospheric pressure over a range of discharge currents from 100 mA to 3 A. The results showed that the increase of the discharge voltage with increasing discharge current was due to increase of the discharge column length which varied with time and the air flow rate and was not due to a positive dynamic characteristic.